The politics of foreign aid in Qatar's foreign policy : an analysis - Bashir, Fadhl Abdullah Omar
This thesis provides a detailed analysis of the State of Qatar’s foreign aid policy (QFAP), during the period from 1995 - 2017, to understand the practice of Muslim donors in general and that of the state of Qatar in particular. Its focus is primarily on development, implementation and evaluation of this policy. To date, there has been little in-depth study of Muslim donors’ behaviours, despite the growing contribution of “Muslim aid” in the global aid regime, as academic scholars mainly focused on exploring the traditional donors’ performance. Besides some other Muslim countries, particularly in the Middle East, Qatar has been involved in aid-giving especially when a new Amir ascended the throne in 1995. To comprehensively explore the research topic, an analytical framework was developed based on the broader literature of policy studies and aid documents including examples of other donors. The data were collected from face-to-face interviews and official documents and publications of the Ministry of Foreign Affairs in Qatar. Additional sources included other local aid institutions and organisations, such as global aid reports from various sources such as the WB and OECD. This thesis explicitly examined the background of Qatar including the domestic and external factors and its foreign policy features as well as its foreign aid policy aspects such as evolution, institutions, legislations, motives and determinants. Subsequently, this study analysed the nature and distribution of Qatari aid and assessed the QFAP in terms of meeting its objectives and aligning with the global aid standards. This research found that the setting of QFAP is clearly influenced by the political system, socio-cultural and economic background of the country as well as its regional and global surroundings. These results make the QFAP consistent with the country’s boarder ambitious foreign policy agenda which is based mainly on political and socio-cultural values with minor economic or elected interests. Besides, the findings show that Qatari aid, which is mainly given in the form of bilateral financial grants, is concentrated in Arab Muslim regions with relatively marginal amounts allocated to other regions. Qatari foreign aid has been prioritised for certain development and humanitarian sectors, especially with the increasing number of crises in neighbouring countries. The QFAP has been successful in achieving various objectives related to the country’s political and humanitarian agendas but failed to fully adhere to global aid frameworks and attain the policy alignment level of its peers. As this thesis recommends potential areas for more exploration such as leadership role in policy and the change in aid behaviour in the region, it calls on QFAP to be technically improved with commendable global measures and practices such as greater transparency and better planning.